An efficient and cost‐effective method for the purification of human basophils. Issue 2 (5th July 2021) - He, Cheng; Gao, Sijia; Zhao, Xinyi; Shi, Yanbiao; Tang, Yanyan; Cao, Yiwei; Bai, Ruixue; Ren, Jinfeng; Zhao, Shuli; Shi, Zhixu; Wang, Hui
Abstract: Human basophils are terminally differentiated granulocytes that are least abundant in the peripheral blood but play important roles in allergic diseases. Studies on human basophils are limited by the high cost on the isolation of human basophils by magnetic‐activated cell sorting (MACS) for negative depletion of non‐basophils, followed by CD123‐based positive selection of basophils. Moreover, such CD123‐based purification of basophils may be limited by blocking of the binding of IL‐3/anti‐CD123 to the surface CD123. Here we identified SSC low CD4 − CD127 − HLA‐DR − CRTH2 high as unique markers for the identification of human basophils through stringent flow cytometric analysis of leukocytes from buffy coat. We established an efficient and cost‐effective method for isolating human basophils from buffy coat based on positive magnetic selection of CRTH2 + cells followed by flow cytometric sorting of SSC low CD4 − CD127 − HLA‐DR − CRTH2 high cells. Approximately 1 to 1.5 million basophils were isolated from one buffy coat with a purity of >97%. Basophils purified by this method were viable and efficiently responded to key regulators of basophils including IL‐3 and anti‐IgE. This method can be used for purifying human basophils for subsequent functional studies.